Update on the diagnosis and treatment of neuromyelits optica spectrum disorders (NMOSD) - revised recommendations of the Neuromyelitis Optica Study Group (NEMOS): Part I: diagnosis and differential diagnosis - Jarius, Sven; Aktas, Orhan; Ayzenberg, Ilya; Bellmann-Strobl, Judith; Berthele, Achim; Giglhuber, Katrin; Häußler, Vivien; Havla, Joachim; Hellwig, Kerstin; Hümmert, Martin W.; Kleiter, Ingo; Klotz, Luisa; et al. (Journal of neurology, 2023)
The term ‘neuromyelitis optica spectrum disorders’ (NMOSD) is used as an umbrella term that refers to aquaporin-4 immunoglobulin G (AQP4-IgG)-positive neuromyelitis optica (NMO) and its formes frustes and to a number of closely related clinical syndromes without AQP4-IgG. NMOSD were originally considered subvariants of multiple sclerosis (MS) but are now widely recognized as disorders in their own right that are distinct from MS with regard to immunopathogenesis, clinical presentation, optimum treatment, and prognosis. In part 1 of this two-part article series, which ties in with our 2014 recommendations, the neuromyelitis optica study group (NEMOS) gives updated recommendations on the diagnosis and differential diagnosis of NMOSD. A key focus is on differentiating NMOSD from MS and from myelin oligodendrocyte glycoprotein antibody-associated encephalomyelitis (MOG-EM; also termed MOG antibody-associated disease, MOGAD), which shares significant similarity with NMOSD with regard to clinical and, partly, radiological presentation, but is a pathogenetically distinct disease. In part 2, we provide updated recommendations on the treatment of NMOSD, covering all newly approved drugs as well as established treatment options.